PENGARUH BRAND IMAGE TERHADAP LOYALITAS WISATAWAN BERBELANJA DI TOKO OLEH-OLEH RAMA KRISNA TUBAN - Raswati, Anggun; Suardana, I Wayan; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 1 (2020): Jurnal IPTA (July 2020), 2020)
Increasing number of tourist will directly give impact to the tourism supporting industrial sector, one of them is Balinese souvenir industry. There are many Balinese souvenir shops in Bali, which make a competition among them becomes more intense, so every company will try to give a better impression for the tourists and try to make them satisfied and make them to visit again. One of the famous Balinese souvenir shop is a souvenir shop of Rama Krisna Tuban. This research aims to determin the influence of Brand Image on tourist loyalty. Respondents in this study amounted to 185 respondents, sample selection using the Purposive sampling method, the data in the study was analyzed using multiple regression analyses assisted by the SPSS statistical version 17.0 for Windows. The results of this research there are three factors that forms the Brand Image and it was found that there was a significant influence between the strength of brand associations on tourist loyalty, there was a significant influence between favorability of brand associations on tourist loyalty, and there was a significant influence between uniqueness of brand associations on tourist loyalty).